2023
DOI: 10.1186/s13018-023-03544-8
|View full text |Cite
|
Sign up to set email alerts
|

One in five patients require conversion to arthroplasty after non-vascularized bone grafts in patients with osteonecrosis of the femoral head: a systematic review

Abstract: Background Non-vascularized bone grafting (NVBG) has demonstrated to treat osteonecrosis of the femoral head (ONFH). There are a number of articles updating the use of NVBG to treat the ONFH, but the percentage of patients subsequently undergoing a total hip arthroplasty (THA) is controversial. Methods Several electronic databases, including PubMed, Embase, Web of Science, and Cochrane databases, were searched to find studies using NVBG to treat ON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…In a retrospective study of long-term glucocorticoid use after bular grafting in patients with femoral head necrosis, Li J et al [13]included 54 patients (96 affected hips), and 21 hips (22%) deteriorated at the last follow-up, of which 8 hips underwent THA. Lau HW et al [15] also found that steroid and alcohol-induced osteonecrosis were more predominant in the graft-failure group, with hazard ratios of 2.33 and 2.07, respectively for graft failure.…”
Section: Analysis and Summary Of Reasons For Hip Preservation Failurementioning
confidence: 99%
“…In a retrospective study of long-term glucocorticoid use after bular grafting in patients with femoral head necrosis, Li J et al [13]included 54 patients (96 affected hips), and 21 hips (22%) deteriorated at the last follow-up, of which 8 hips underwent THA. Lau HW et al [15] also found that steroid and alcohol-induced osteonecrosis were more predominant in the graft-failure group, with hazard ratios of 2.33 and 2.07, respectively for graft failure.…”
Section: Analysis and Summary Of Reasons For Hip Preservation Failurementioning
confidence: 99%